Conversion of 3D data objects into IGES - Mohamad Faiez Rosli. (2014)
This paper is focused on the conversion of 3D data generated by a 2d recovery program into IGES format, thus enabling it to be read by the IGES processor of a CAD system, Solidworks. IGES file format is highlighted, along with the various entity type involved in the conversion . C++ language, as the selected medium for programming the translator, is discussed along with the standard C++ library. The steps taken to create the translator are presented chronologically, initializing at creating an IGES file, and leading up to the final program. Results will then be analyzed and recommendations are provided for future developments.